Atty at law - Lockette, Tim (Triangle Square Books for Young Readers, 2020)
Atticus "Atty" Peale is named after her father's favorite fictional character, a lawyer in a famous book. When Atty tries to save the life of a dog in the animal shelter where she volunteers, she ends up arguing for the dog's life in court, inspiring her to speak up for those who don't have a voice. As her dad teaches her law basics, Atty gets involved in his current case defending an illiterate man on a murder charge. When strange occurrences begin to threaten Atty's attempts to help her dad, Atty is determined to find the truth, as well as navigate the strange social scene of seventh grade.